2026 Richard Hader Visionary Leader Award Call for Entries (Nursing Management, 2026)
Aim The aim of this project is to invite people across communities and disciplines to consider both the systemic drivers of the Earth crisis and their own potential to lead and contribute to meaningful change, while exploring shared narratives that deepen understanding of global interdependence and nurture leadership grounded in equity, care and inclusion. Methods Grounded in the Movement Building and Systems Change domain of the Planetary Health Education Framework, this qualitative, participatory storytelling initiative gathered diverse global narratives that illuminate lived experiences of environmental change and action. Insights Shared stories foster empathy, collective identity and hope, demonstrating how leadership often begins with personal awakening and expands towards a sense of shared responsibility. Indigenous, local, community-based and academic examples illustrate leadership expressed through everyday stewardship, community initiatives and institutional change, challenging narrow or hierarchical definitions of success. Conclusions These narratives show that effective Planetary Health leadership is context-dependent, often incremental and strengthened by recognising diverse pathways to action rooted in equity, inclusion and care.